(untitled) - Goljan, Edward F. (Philadelphia, Pa., 2014)
Makes it easy for you to master all of the pathology material covered on the USMLE Step 1. This book combines an outline-format review of key concepts and hundreds of full-color images and margin notes, and more than 400 USMLE-style online questions.
Keywords: Bệnh lý,Pathology; Câu hỏi thi,Examination questions